2003
DOI: 10.1530/rep.0.1260049
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive responses of mice immunized with purified recombinant mouse zona pellucida subunit 3 (mZP3) proteins

Abstract: Mouse zona pellucida subunit 3 (mZP3) was tested for efficacy as an immunocontraceptive antigen by comparing the fertility of mice immunized with recombinant mZP3 proteins. Recombinant protein was expressed using either the vaccinia virus T7 mammalian (vmZP3 protein) or baculovirus insect cell (bmZP3 protein)-expression systems. Female BALB/c or wild mice were immunized by i.p. injection using Freund's complete adjuvant and boosted three times with affinity purified recombinant proteins in Freund's incomplete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
(13 reference statements)
2
9
2
Order By: Relevance
“…It appears that there is no correlation between the levels of total IgG antibody and infertility in mice immunized with different regimens except the co‐immunized group. This is similar to reports that not only does the level of IgG antibodies not appear to be associated with infertility, but also there is no correlation between IgG1 or IgG2a antibodies and infertility in mice immunized with recombinant ZP3 proteins or inoculated with murine cytomegalovirus expressing the mZP3 gene 11, 12, 14. However, antibodies against ZP3 are important for infertility as demonstrated in several other studies that high titers of total IgG are associated with infertility in mice immunized with ZP3 peptides or with a recombinant ectromelia virus expressing the mZP3 gene 13, 24, 25.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It appears that there is no correlation between the levels of total IgG antibody and infertility in mice immunized with different regimens except the co‐immunized group. This is similar to reports that not only does the level of IgG antibodies not appear to be associated with infertility, but also there is no correlation between IgG1 or IgG2a antibodies and infertility in mice immunized with recombinant ZP3 proteins or inoculated with murine cytomegalovirus expressing the mZP3 gene 11, 12, 14. However, antibodies against ZP3 are important for infertility as demonstrated in several other studies that high titers of total IgG are associated with infertility in mice immunized with ZP3 peptides or with a recombinant ectromelia virus expressing the mZP3 gene 13, 24, 25.…”
Section: Discussionsupporting
confidence: 90%
“…Sperm‐egg binding can be blocked by importing another ligand for receptor sites such as antibodies of ZP3 and prevent fertilization. Several studies have demonstrated that vaccines formulated with either native or recombinant ZP antigens can suppress fertility effectively following an active immunization 8–12. However, there is much accumulating evidence to suggest that this approach is associated with adverse autoimmune reactions in the ovaries leading to a deleterious effect on ovarian function 8, 9, 12–14.…”
Section: Introductionmentioning
confidence: 99%
“…Another issue is how fertility responses in trials such as these may differ from those of the final bait-delivered product as a result of differences in route of immunisation, dose, and antigen presentation. For example, the effects on fertility in mice differ significantly between intramuscular immunisation with recombinant mouse ZP3 and infection with mouse cytomegalovirus expressing mouse ZP3 (Hardy et al 2003;Lloyd et al 2003). Ultimately, a wider range of non-target species will have to be tested to satisfy regulatory requirements before a bait-delivered fertility vaccine could be deployed.…”
Section: Discussionmentioning
confidence: 99%
“…Mice immunised with recombinant mouse ZP3 expressed from a mammalian cell-expression system show reduced fertility (Hardy et al 2003), and this effect has been traced, at least in part, to a specific 15-21-amino-acid epitope of the protein (Millar et al 1989;Lou et al 1995;Hardy et al 2002Hardy et al , 2003. The initial hypothesis was that this epitope was a sperm-binding 'receptor'.…”
Section: Introductionmentioning
confidence: 99%
“…2003), Chinese hamster ovary (CHO) systems (Zhao et al. 2004), plant systems (Tacket 2005), viral systems (Hardy et al. 2003), insect systems (Hardy et al.…”
Section: Zona Pellucida (Zp) Vaccinesmentioning
confidence: 99%